Comprehensive Quality Evaluation of American Ginseng for Different Parts and Abnormal Trait Based on the Major Ginsenoside Contents and Morphological Characteristics. (25th March 2021) - Yu, Jingping; Xu, Tong; Lin, Haiyan; Lin, Ying; Zhou, Jie; Zhang, Yongqing
Abstract : The demand for American ginseng, a famous traditional medicine and high-grade healthy food, has increased dramatically over recent years. However, only the main root is popular among consumers, whereas other parts of American ginseng are rarely available in the market. In this study, the contents of 5 major ginsenosides (Re, Rc, Rg1, Rd, and Rb1 ) were determined through high-performance liquid chromatography. Our study showed that all these 5 major ginsenosides are found in different parts of American ginseng plants, and the total content in different parts varied significantly in the following order: fibrous root > flower > branch root > main root > leaf > stem . Interestingly, the total content in the fibrous root was approximately 2.24 times higher than that in the main root. Further research indicated that the ginsenoside content in American ginseng with abnormal characteristics (physical deformity caused by disease and discolouration) is similar to that in the normal plant. Interestingly, a positive correlation was observed between the main root diameter and total ginsenoside content, whereas a negative correlation was observed between the main root length and total ginsenoside content. Our comprehensive study revealed that all parts of American ginseng, including the main root with abnormal characteristics, possess medicinal or economic value. Therefore, our results provide feasible evidence to further explore the potential application of American ginseng.